Pengelolaan Perkuliahan Character Building yang Berorientasi pada Peningkatan Kepuasan Pelanggan di Binus University - Stephanus Ngamanken (Bina Nusantara University, 2014)
This study focuses on the improvement of customer satisfaction through good governance of Character Building course in Bina Nusantara University (Binus). CBDC as the department which organizes Character Building (CB) in Binus makes continuous improvements in all aspects in organizing CB. The purpose of this research as a partnership with CBDC is to look for and find the needs, desires, and expectations (importance) of students as customers about classroom managemant of CB in Binus. The research method used is Community Survey. Comunity Survey was conducted in 02PDO class at second semester of 2012/2013 academic year. Results of the research from 25 surveyed items show there are 13 items that students expected to get in the course but they did not get. There are 9 items that they expected to get in the course and they got. Moreover, there are 3 items that they did not expect to get in the course, but they got. Research concludes, in implementation of Character Building course in 02PDO class at second semester of 2012/2013 academic year, that there were 13-student expectation not fulfilled; 9-student expectation fulfilled; and 3 items not expected yet given in the lecture.